Perubahan Penggunaan Lahan dan Pengaruhnya Terhadap Koefisien Regim Sungai di DAS Kemoning Kabupaten Sampang - Kurniawan, Agus Eko; Purnaweni, Hartuti; Suripin, Suripin (Universitas Riau, 2015)
Studies of changes in land use is essential in the kemoning watershed Sampangregency of East Java Province, due to changes in land use have an impact on the physicalenvironment, social and economic, including its impact on flooding. The purpose of this studywas to analyze changes in land use, using satellite imagery, GIS and cross tabulation,analyzing changes in precipitation computed arithmatik method to obtain the average rainfallin 2004, 2009, and 2013. Analyzing the dynamics of the discharge in the kemoning watershed2004, 2009 and 2013 FJ. Mock method. Analyzing changes in land use and its impact on theriver regime coefficient kemoning watershed. The study states that the decline in land area forforest, mixed garden, open land, mangrove, wetland, scrub, and an increase in landsettlements, field / fields and ponds. The amount of rainfall and flow rates tend to increasefrom 2004 to 2013, as well as the highest rainfall. Coefficient of river regime generally showpoor state of the watershed from 2004 to 2013. Changes in land use of open land (forests,orchard or fields) into land for settlement leads to reduced surface water infiltration,increase runoff, and reduce groundwater recharge it is very influential on the river regimecoefficient. It is an indicator of the environmental damage has occurred to the hydrologicalfunctions, namely a decrease in soil water availability because of the rain water is wasted,and only partially infiltrated into the ground.